Tripartite Cooperation in Assigning ETDs with DOIs - A Practical Experience of National Taiwan Normal University Library - Yu, Chiu-Yun; Ke, Hao-Ren (Cadernos BAD, 2020)
National Taiwan Normal University (NTNU) Library was trying to engage two different vendors to cooperate and set up the Digital Object Identifier (DOI) to improve international visibilities of students’ ETDs. This Practical Experience aims to share a valuable lesson through tripartite cooperation, and firmly believe other institutions can benefit from our experience to save time and effort spent on the launch of such cooperation.